Alat Penyempot Pestisida Tenaga Surya Menggunakan Panel Surya 30W - Edi Sarwono; Subiyanto Subiyanto; Yohanes Primadiyono; Riana Defi Mahadji Putri; Ari Dwi Prasetio; Asriningati Asriningati; Fahimatul Ilmi (Journal of Electrical Power Control and Automation (JEPCA), 2021)
Pesticide sprayer tools that are widely used by farmers are still using hands or fossil fuel machines, so they are still classified as traditional and ineffective methods. Some of the weaknesses of the traditional method include less practical, fossil fuels that will run out and the impact on the environment. Solar energy from the sun can be a solution to these problems. Solar panels are devices used to convert sunlight into electrical energy. In this study, a monocrystalline 30W solar panel was used as a tool used to capture sunlight. By utilizing solar power as an energy source sprayer and pump so that it can take advantage of the hand pressing the lever and refilling it manually. In addition, preferring solar power over fossil fuel engines can reduce the use of fossil fuels and further strengthen renewable energy that will not run out and is environmentally friendly. In this study, solar panels were installed above the head to maximize the capture of sunlight and also protect the head from the heat of the sun. The results showed that the battery energy required to spray the difference in battery percentage from 10 liters to 6 liters of liquid volume was 4% and from 6 liters to 2 liters of liquid volume was 6%.